The Effect of Health Services Marketing Mix on Patient Loyalty With Patient Trust As an Intervening Variable (Case Study at Tanjungsiang Health Center) - Sinta DANIAWATI F; M MUHARDI; Dedy Ansari HARAHAP (International Journal of Environmental, Sustainability, and Social Science, 2023)
The Purpose of this study was to determine: (1) to obtain findings regarding the effect of the marketing mix on patient trust at the Puskesmas Tanjungsiang (2) to obtain findings regarding the effect of the marketing mix on patient loyalty at Tanjungsiang Health Center (3) To obtain findings regarding the effect of trust on patient loyalty at Tanjungsiang Health Center (4) To obtain findings regarding the effect of marketing mix on patient loyalty through trust at the Tanjungsiang Health Center. The research method used in this research is quantitative and the type of research is descriptive verification. The sampling technique used was purposive sampling, namely 140 patients who had visited the Tanjungsiang Health Center >2 times. The analysis technique uses path analysis. The results of this study are the Marketing Mix has a significant positive effect on Patient Trust, the Marketing Mix has a significant positive influence on Patient Loyalty, Patient Trust has a significant positive influence on Patient Loyalty and There is a significant positive influence on the Marketing Mix to Patient Loyalty through Trust at Tanjungsiang Health Center.